Insights Into the Ecological Role of Pseudomonas spp. in an Ant-plant Symbiosis - Fukuda, Taise T. H.; Pereira, Camila F.; Melo, Weilan G. P.; Menegatti, Carla; Andrade, Paulo H. M.; Groppo, Milton; Lacava, Paulo T.; Currie, Cameron R.; Pupo, Mônica T. (Frontiers in Microbiology, 2021)
In the myrmecophytic mutualistic relationship between Azteca ants and Cecropia plants both species receive protection and exchange nutrients. The presence of microorganisms in this symbiotic system has been reported, and the symbiotic role of some fungi involved in the myrmecophytic interactions has been described. In this work we focus on bacteria within this mutualism, conducting isolations and screening for antimicrobial activities, genome sequencing, and biochemical characterization. We show that Pantoea, Rhizobium, Methylobacterium, Streptomyces and Pseudomonas are the most common cultivable genera of bacteria. Interestingly, Pseudomonas spp. isolates showed potent activity against 83% of the pathogens tested in our antimicrobial activity assays, including a phytopathogenic fungus isolated from Cecropia samples. Given the predicted nitrogen limitations associated with the fungal patches within this myrmecophyte, we performed nitrogen fixation analyses on the bacterial isolates within the Proteobacteria and show the potential for nitrogen fixation in Pseudomonas strains. The genome of one Pseudomonas strain was sequenced and analyzed. The gene cluster involved in the biosynthesis of cyclic lipodepsipeptides (CLPs) was identified, and we identified mutations that may be related to the loss of function in the dual epimerization/condensation domains. The compound was isolated, and its structure was determined, corresponding to the antifungal viscosinamide. Our findings of diazotrophy and production of viscosinamide in multiple Pseudomonas isolates suggests that this bacterial genus may play an important role in the Cecropia-Azteca symbiosis.